Study of plasma protein C and inflammatory pathways: Biomarkers for dimethylnitrosamine-induced liver fibrosis in rats - Saha, Joy K.; Xia, Jinqi; Sandusky, George E.; Chen, Yun-Fei; Gerlitz, Bruce; Grinnell, Brian; Jakubowski, Joseph A. (European journal of pharmacology, 2007)
The present investigation was designed to identify potential biomarker(s) and assess the involvement of inflammatory pathway in dimethylnitrosamine (DMN)-induced liver fibrosis in rats. Following DMN-treatment (10 mg/ml/kg, i.p., given three consecutive days each week for 4 weeks) body and liver weights were significantly decreased concurrent with increasing severity of liver damage assessed by bridging fibrosis, a histopathologic assessment and characteristic of human liver disease. Protein C along with albumin, C-reactive-protein (CRP), haptoglobin and total protein were significantly reduced and correlated with changes in liver histopathology. Biochemical markers of liver functions were significantly increased and correlated with changes in liver histopathology and plasma levels of protein C. Soluble intracellular-adhesion-molecule-1 (sICAM-1) levels were increased significantly but were poorly correlated with histopathology and protein C levels. Inflammatory chemokines and other analytes, monocyte-chemoattractant-protein-1 and 3 (MCP-1 and MCP-3), macrophage-colony-stimulating-factor (M-CSF) were significantly increased during the disease progression, whereas macrophage-derived-chemokine (MDC) and CRP were significantly suppressed. Circulating neutrophils and monocytes were also increased along with disease progression. The differential changes in sICAM-1, hyaluronic acid, gamma-glutamyltranspeptidase (GGT), neutrophil and other inflammatory chemokines suggest the involvement of inflammatory pathways in DMN-induced liver fibrosis. In conclusion, the progressive changes in protein C along with other noninvasive biochemical parameters whose levels were significantly correlated with disease progression may serve as biomarkers for pharmacological assessment of targeted therapy for liver fibrosis.